2019
DOI: 10.1111/cas.14129
|View full text |Cite
|
Sign up to set email alerts
|

Mucin 21 is a key molecule involved in the incohesive growth pattern in lung adenocarcinoma

Abstract: Decreased cell adhesion has been reported as a significant negative prognostic factor of lung cancer. However, the molecular mechanisms responsible for the cell incohesiveness in lung cancer have not yet been elucidated in detail. We herein describe a rare histological variant of lung adenocarcinoma consisting almost entirely of individual cancer cells spreading in alveolar spaces in an incohesive pattern. A whole exome analysis of this case showed no genomic abnormalities in CDH1 or other genes encoding cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…However, in addition to roles as epithelial protectants, mucins and related proteins also serve roles in cell signaling with physiological consequences. This is recently shown for MUC21 overexpression as influencing the development of lung adenocarcinoma [ 78 ] and TFF1 influencing epithelial-mesenchymal transition. Together, this may be a contributing factor to the STRING cluster of keratinocyte differentiation factors discussed below, but further study is warranted to determine which cell types are expressing these genes and which cell signaling may be impacted.…”
Section: Discussionmentioning
confidence: 68%
“…However, in addition to roles as epithelial protectants, mucins and related proteins also serve roles in cell signaling with physiological consequences. This is recently shown for MUC21 overexpression as influencing the development of lung adenocarcinoma [ 78 ] and TFF1 influencing epithelial-mesenchymal transition. Together, this may be a contributing factor to the STRING cluster of keratinocyte differentiation factors discussed below, but further study is warranted to determine which cell types are expressing these genes and which cell signaling may be impacted.…”
Section: Discussionmentioning
confidence: 68%
“…However, in addition to roles as epithelial protectants, mucins and related proteins also serve roles in cell signaling with physiological consequences. This is recently shown for MUC21 overexpression as in uencing the development of lung adenocarcinoma (89) and TFF1 in uencing epithelial-mesenchymal transition. Together, this may be a contributing factor to the STRING cluster of keratinocyte differentiation factors discussed below, but further study is warranted to determine which cell types are expressing these genes and which cell signaling may be impacted.…”
Section: Discussionmentioning
confidence: 59%
“…In recent years, correlation studies showed an association between mucin overexpression and glycosylation with cancer formation, prognosis, and metastasis (Behera et al, 2015). MUC 1, 2, 3, 5AC, 5B, 8, 16, and 21 are related, to a different degree, in breast (Masaki et al, 1999), ovarian (Yin and Lloyd, 2001; Wang and El-Bahrawy, 2015), endometrial tumors (Hebbar et al, 2005), prostate (Xiong et al, 2006), pancreatic (Levi et al, 2004), gastric and cervical (Kaur et al, 2013), colorectal (Chang et al, 1994), renal cell carcinoma (Leroy et al, 2002), pseudoxyoma periotonei (Ciriza et al, 2000), and recently studied lung cancer (Yoshimoto et al, 2019). There are multiple recent reviews about the role on mucins and cancer for further reading (Chugh et al, 2015; Dhanisha et al, 2018; Kasprzak and Adamek, 2019).…”
Section: Mucins Mlms and Diseasesmentioning
confidence: 99%